An Assistive Soft Wrist Exosuit for Flexion Movements With an Ergonomic Reinforced Glove - Chiaradia, Domenico; Tiseni, Luca; Xiloyannis, Michele; Solazzi, Massimiliano; Masia, Lorenzo; Frisoli, Antonio (Frontiers in Robotics and AI, 2021)
Soft exosuits are a promising solution for the assistance and augmentation of human motor abilities in the industrial field, where the use of more symbiotic wearable robots can avoid excessive worker fatigue and improve the quality of the work. One of the challenges in the design of soft exosuits is the choice of the right amount of softness to balance load transfer, ergonomics, and weight. This article presents a cable-driven based soft wrist exosuit for flexion assistance with the use of an ergonomic reinforced glove. The flexible and highly compliant 3D printed plastic structure that is sewn on the glove allows an optimal force transfer from the remotely located motor to the wrist articulation and to preserve a high level of comfort for the user during assistance. The device is shown to reduce fatigue and the muscular effort required for holding and lifting loads in healthy subjects, for weights up to 3 kg.